Historicizing the Lived Masculinities in a Postpartitioned Metropolis. (October 2019) - Das, Arnab
The autoethnographic narrative seeks to historicize the major political episodes of Calcutta/Kolkata metropolis as the meeting point of personal and public contexts of meaning since India's independence. This juxtaposition has emerged to be even more significant due to the partition of Bengal, India. The middle-class majority framework of everyday life in the city shifted from the closed class hegemony of the bhadralok masculinity to the postpartitioned position of open and inclusive masculinity, which encountered unprecedented challenges in terms of caste, gender, and class. For theorizing such masculinities (e.g., feudal, radical, coercive, conjugated, and pragmatic) in these periods, the personal is found to be related to the public, the subaltern is found to be related to the hegemonic, and the political enters critically the continuum of the domestic and the public. Despite the growing autonomy of women since the colonial period (until it reached the scope of accepted practice in the postcolonial period), the deeply embedded patriarchy at the level of the family privileged masculinity as the only legitimate manifestation of hegemonic power in the public practices of any order of society. Bengalis could not come out of this masculine fold in spite of a militancy invoked for survival, encounters with radical movements, political turbulence, and the pragmatic governance of the populace for a long period.